Rare but not forgotten: A case of meningitis due to ceftriaxone-resistant Streptococcus pneumoniae - Naomi Hauser; Miguel E. Cervera-Hernandez; John Lonks; Najam Zaidi (IDCases, 2018)
Despite the dramatic decrease in invasive pneumococcal disease since the widespread use of the first pneumococcal vaccine, invasive and resistant disease still occurs. We present a case of ceftriaxone-resistant pneumococcal meningitis suggesting that continued vigilance is warranted for empiric treatment of meningitis when Streptococcus pneumoniae is a concern.